Neuroscience for Organizational Communication A Guide for Communicators and Leaders - McHale, Laura (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
"A terrific guide to this emerging field, with practical applications that communicators and leaders can use right away." - Srini Pillay, M.D., CEO of NeuroBusiness Group; Author of Tinker Dabble Doodle Try: Unlock the Power of the Unfocused Mind "As a neuroscientist, I deeply enjoyed McHale's use of language and fluid style to make complex research accessible. She stays relevant and recent helping to explain Zoom fatigue and somatic mind-body links. Read it!" - Richard Boyatzis, PhD, Distinguished University Professor, Case Western Reserve University; Co-author of the international bestseller Primal Leadership and the new Helping People Change "Dr. McHale provides actionable insights into the way our brains function on communications and how to fire up leaders and followers alike." - Tamara L. Gillis, Ed.D., ABC, IABC Fellow, FRSA; Editor, The IABC Guide for Practical Business Communication Organizational communication is at a crossroads and professional communicators and leaders alike need to up their game. In this insightful and practical guide, leadership psychologist Dr. Laura McHale shows how neuroscience can help, surveying the field to reveal the research that is most applicable to organizations and providing an evidence-based approach to dramatically boost the effectiveness and impact of communications. From structural dynamics to occupational aprosodia, from the threat (and opportunities) of GPT-3 to the neuroscience of Zoom fatigue, she takes the reader on a fascinating journey of how neuroscience can help unlock the potential of communicators and the organizations they work for. Dr. Laura McHale (PsyD, CPsychol, ABC) is a leadership psychologist, author, and consultant specializing in leader development, neuroscience, communication, and organizational culture. She is the founder of Conduit Consultants, whose mission is to enable generative dialogue that leads to lasting change in individuals and organizations. Prior to becoming a psychologist, Dr. McHale worked for over 15 years as a corporate communications executive in the financial services industry, across the US, Europe, and Asia. She resides in Hong Kong.
Part 1. Introduction to neuroscience for corporate communications -- Chapter 1. Why should communicators care about neuroscience? - Chapter 2. The changing landscape -- Chapter 3. Let's get neurological -- Chapter 4. The body politic -- Part 2. The neurocommunicator's toolkit -- Chapter 5. The coming of neuroleadership -- Chapter 6. The braking system -- Chapter 7. The toolkit -- Chapter 8. The neuroscience of Aristotle -- Chapter 9. The culture club -- Part 3. The psychology of the corporate communications team -- Chapter 10. Communicator, heal thyself -- Chapter 11. Safe space -- Part 4. Self-care for corporate communications professionals -- Chapter 12. Communicating trauma and loss -- Chapter 13. The neuroscience of compassion -- Epilogue. Practice what you preach.
Keywords: Management; Neurosciences; Personnel management; Management; Neuroscience; Human Resource Management